KEABSAHAN ANAK DI LUAR PERKAWINAN (Analisis terhadap putusan MK Nomor 46/PUU-VIII/2010) - Baihaki Baihaki (AL-ILMU, 2022)
Based on preventive theory (Dar'ul mufasid muqaddam ala Jalbil Mashalih). This paper tends to the legitimacy of children out of wedlock (Analysis of the Constitutional Court's decision Number 46/PUU-VII/2010). The source of the data obtained is through empirical law research. Through data analysis and discussion, research shows that the Constitutional Court's decision on the status of children outside of marriage is not a child resulting from an adulterous relationship but from a legal marriage, but carried out outside the procedure. The Chief Justice of the Constitutional Court, Mahmud Md, in the Jawa Pos newspaper, clarified the Constitutional Court's decision by saying: That what the assembly meant by the phrase "children out of wedlock" was not a child resulting from adultery but a child resulting from an unregistered marriage.